Understanding the role of rural non-farm enterprises in Africa’s economic transformation: Evidence from Tanzania - Diao, Xinshen; Magalhaes, Eduardo; McMillan, Margaret S. (Routledge, 2018)
Tanzania’s recent growth boom has been accompanied by a threefold increase in the share of the rural labour force working in nonfarm employment. Although households with nonfarm enterprises are less likely to be poor, a substantial fraction of these households fall below the poverty line. Heterogeneity in the labour productivity of rural nonfarm businesses calls for a two-pronged strategy for rural transformation. Relatively unproductive enterprises may be part of a poverty reduction strategy but should not be expected to contribute to employment and labour productivity growth. Failure to account for this heterogeneity is likely to lead to disappointing outcomes.